Preservation of small extracellular vesicles for functional analysis and therapeutic applications: a comparative evaluation of storage conditions - Jun-Yong Wu; Yong-Jiang Li; Xiong-Bin Hu; Si Huang; Da-Xiong Xiang (Taylor & Francis Group, 2021)
Extracellular vesicles (EVs) are nanovesicles involved in multiple biological functions. Small EVs (sEVs) are emerging as therapeutics and drug delivery systems for their contents, natural carrier properties, and nanoscale size. Despite various clinical application potentials, little is known about the effects of storage conditions on sEVs for functional analysis and therapeutic use. In this study, we evaluated the stability of sEVs stored at 4 °C, −20 °C, and −80 °C up to 28 days and compared them to fresh sEVs. Also, the effect of freeze-thawing circles on the quantity of sEVs was assessed. We found that different storage temperatures, along with shelf life, impact the stability of sEVs when compared to freshly isolated sEVs. Storage changes the size distribution, decreases quantity and contents, and impacts cellular uptake and biodistribution of sEVs. For functional studies, isolated sEVs are suggested to be analyzed freshly or stored at 4 °C or −20 °C for short-term preservation depending on study design; but −80 °C condition would be more preferable for long-term preservation of sEVs for therapeutic application.